The composition of video games : narrative, aesthetics, rhetoric and play - Quijano, Johansen (Studies in gaming., 2019)
"Video games are a complex, compelling medium in which established art forms intersect with technology to create an interactive text. Visual arts, architectural design, music, narrative and rules of play all find a place within, and are constrained by, computer systems whose purpose is to create an immersive player experience. In the relatively short life of video game studies, many authors have approached the question of how games function, some focusing on technical aspects of game design, others on rules of play. Taking a holistic view, this study explores how ludology, narratology, visual rhetoric, musical theory and player psychology work (or don't work) together to create a cohesive experience and to provide a unified framework for understanding video games."--